Absorbing Technology: Translation Pedagogy and Networked-Communication Culture - Williams, Donna (Meta, 2003)
AbstractNew translation students have often spent most of their lives using computers and the Internet. Their expectations regarding information accessibility in turn affect the culture of the translation classroom. In this article I examine simple ways of appropriating networked communication for a type of translation teaching that takes into account an Internet-based model of information flow. I also advocate a movement toward student-centred learning.